CO2/CH4 TRANSPORT IN POLYPERFLUOROSULFONATE IONOMERS - EFFECTS OF POLAR-SOLVENTS ON PERMEATION AND SOLUBILITY - PELLEGRINO, J; KANG, YS (ELSEVIER SCIENCE BV, 1995)
We measured CO2 and CH4 gas permeation through polyperfluorosulfonate ionomer (PFSI) that was solvated with water, methanol, ethanol, or 1-propanol. These measurements were compared with predictions based on a two-phase, effective-media, membrane model that considered a number of possible geometries for the distributed phase (the ionic clusters). The transport parameters (solubility and diffusivity) for each of the phases and the volume fraction of dispersed phase were either measured independently or estimated from prior literature data. We were unable to match all the experimental observations with this two-phase model. We conclude that different polar solvents can incorporate themselves into the flourocarbon 'continuous phase' in ways that will alter the effective diffusion coefficient of that phase to gas permeation.
Keywords: ION-EXCHANGE MEMBRANES; FACILITATED TRANSPORT; NAFION MEMBRANES; LIQUID-MIXTURES; SEPARATION; COUNTERIONS; FILMS